The Doctrine of Natural Justice as an Arm of the Rule of Law in Nigeria - Etudaiye, Muhtar Adeiza (Journal of Malaysian and Comparative Law, 2007)
The principle of natural justice has featured prominently in decisions by judicial, quasi-judicial and administrative bodies affecting Nigerian citizens. Yet, in view of the high level of illiteracy in Nigeria coupled with a general lack of enlightenment regarding the rights of the citizen, most Nigerians are hardly aware what these rights and the principles behind them entail. This paper is geared towards shedding some light on those rights and principles.